Legal Certainty of Oil Palm Plantation Cultivation Rights within Forest Areas Following Government Regulation Number 45 of 2025 - Wardhana, Wisnu Eka; Sri Wahyu Handayani (Al-Risalah, 2026)
Government Regulation Number 45 of 2025 concerning the Amendment to Government Regulation Number 24 of 2021 on Procedures for the Imposition of Administrative Sanctions in the Forestry Sector was enacted as an instrument to address oil palm plantations that have encroached upon forest areas. However, rather than providing legal certainty, this regulation introduces a "reclamation" mechanism that potentially revokes Land Cultivation Rights (Hak Guna Usaha/HGU) that were lawfully obtained under the Basic Agrarian Law Number 5 of 1960. This study aims to analyze the legal certainty of HGU for oil palm plantations within forest areas following the enactment of Government Regulation Number 45 of 2025, and to identify potential normative conflicts arising within Indonesia's agrarian legal framework. The research employs a normative juridical method with a statute approach and a conceptual approach. The findings reveal that Government Regulation Number 45 of 2025 violates at least four of Lon Fuller's eight principles of the inner morality of law, namely the principles of non-retroactivity, non-contradiction, possibility of compliance, and congruence. Furthermore, the land reclamation mechanism contradicts Articles 18 and 34 of the Basic Agrarian Law, which exhaustively enumerate the lawful grounds for the revocation of land rights, and departs from the ultimum remedium principle established under Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law. The empowerment of the Forest Area Enforcement Task Force (Satgas PKH) as an ad hoc institution with authority equivalent to the Minister of Forestry also contravenes the principle of institutional legality. This study recommends a comprehensive revision of Government Regulation Number 45 of 2025, the definitive completion of forest area demarcation, and the restoration of enforcement authority to the institutions mandated by law.